Evaluation and Pre-selection of New Grapevine Genotypes Resistant to Downy and Powdery Mildew, Obtained by Cross-Breeding Programs in Spain - Ruiz-García, Leonor; Gago, Pilar; Martínez-Mora, Celia; Santiago, José Luis; Fernádez-López, Diego J.; Martínez, María del Carmen; Boso, Susana (Frontiers in Plant Science, 2021)
The need to develop an environmentally friendly, sustainable viticulture model has led to numerous grapevine improvement programmes aiming to increase resistance to downy and powdery mildew. The success of such programmes relies on the availability of protocols that can quantify the resistance/susceptibility of new genotypes, and on the existence of molecular markers of resistance loci that can aid in the selection process. The present work assesses the degree of phenotypic resistance/susceptibility to downy and powdery mildew of 28 new genotypes obtained from crosses between ‘Monastrell’ and ‘Regent’. Three genotypes showed strong combined resistance, making them good candidates for future crosses with other sources of resistance to these diseases (pyramiding). In general, laboratory and glasshouse assessments of resistance at the phenotype level agreed with the resistance expected from the presence of resistance-associated alleles of simple sequence repeat (SSR) markers for the loci Rpv3 and Ren3 (inherited from ‘Regent’), confirming their usefulness as indicators of likely resistance to downy and powdery mildew respectively, particularly so for downy mildew.